Societal Trust and Management Earnings Forecasts - Guan, Yuyan; Lobo, Gerald J.; Tsang, Albert; Xin, Xiangang (The Accounting Review, 2020)
ABSTRACT We investigate the relationship between societal trust and managers' decisions to voluntarily issue earnings forecasts. We reason that managers are more likely to issue earnings forecasts in high-trust countries than in low-trust countries because investors view these voluntary disclosures as more credible information about the firm's future profitability. We find evidence consistent with these predictions, suggesting that societal trust fosters corporate voluntary disclosure. We also document that societal trust works as a substitute for country-level formal institutions in terms of its implications for management earnings forecast (MEF) issuance. Additionally, we find a stronger relationship between firm-level commitment to credible disclosure and MEFs in low-trust countries, suggesting that country-level societal trust relates to the effectiveness of firm-level credibility-enhancing mechanisms. Finally, we show that firms from countries with higher societal trust issue more precise and accurate MEFs that contain more information about multiple items.